Research of closed-loop voltage and speed regulation method based on six-pulse-wave AC/AC frequency converter - LI Gao-ju; DU Qing-na (Gong-kuang zidonghua, 2013)
In view of problem of bigger speed difference between frequency levels in high frequencies in speed regulation technology of six-pulse-wave AC/AC frequency converter, the paper proposed a closed-loop voltage and speed regulation method based on six-pulse-wave AC/AC frequency converter. The method sets many voltage levels between two high frequencies, and changes output voltage of AC/AC frequency converter to realize closed-loop step voltage and speed regulation of the AC/AC frequency converter. The simulation and experimental results show that the method can use memory space effectively, expands speed regulation range of the AC/AC frequency converter, and has good speed regulation effect.